PENGEMBANGAN GAME EDUKASI KARTU AKSI BAIK VS BURUK DENGAN MODEL 4D UNTUK MENANAMKAN PERILAKU RAMAH LINGKUNGAN TERKAIT PERUBAHAN IKLIM PADA SISWA KELAS 4 SD DI PKBM EDUHOUSE SEMARANG - Wahyu Sudrajat, Andy; Zulfikasari, Sony (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Environmental education regarding climate change at PKBM EduHouse Semarang faces significant challenges due to the lack of interactive learning media and gadget distractions that hinder student focus. This study aims to develop a valid and practical physical learning media in the form of the "Good Action vs. Bad Action" Educational Card Game for 4th-grade students. The research method employed is Research and Development (R&D) referring to the 4D development model (Define, Design, Develop, Disseminate) which was carried out with limited dissemination. Data collection techniques included interviews, observations, and validation questionnaires. The product feasibility was tested by media experts, material experts, and user perception tests (facilitators). The results showed that the developed media was declared "Very Feasible" with a validation score of 95.65% from media experts and 86.0% from material experts. Furthermore, the user perception test obtained a score of 80.0% with the "Very Feasible" category. Based on these findings, it can be concluded that the Educational Card Game is effective and feasible to be used as a learning medium to instill eco-friendly behavior concretely and reduce student dependence on gadgets.